Transport infrastructure and economic growth: Panel data approach for Armenia, Georgia and Turkey - Gohar Badalyan; Thomas Herzfeld; Miroslava Rajcaniova (Review of Agricultural and Applied Economics, 2014)
Provision of efficient, reliable, and affordable infrastructure is essential for economic growth. Transportation infrastructure in particular, is vital to the prosperity of regions. To investigate the relationship and the direction of causality between transport infrastructure, investment in infrastructure and economic growth, we use panel cointegration analysis and panel causality analysis for three countries Armenia, Turkey, and Georgia. We use annual data of Armenia, Turkey and Georgia for the period 1982-2010.The tests proved the existence of more than one cointegrating vector indicating that the system under examination is stationary in more than one direction. The VECM results showed that gross capital formation and road/rail goods transported have a positive and statistically significant impact on economic growth in the short- run. Overall, the existence of bidirectional causality between economic growth and infrastructure investment, and between road and rail passengers carried and infrastructure investment was indicated in both the short and long-run.
Keywords: H54; O18; 330; economic growth; transport infrastructure; panel cointegration; VECM